<span>0=2x+3(3x-4)-(-x+14)
Follow BEDMAS
</span><span>0=2x+9x-12-(-x+14)
</span>0=2x+9x-12+x-14
Add like terms
0=11x-12+x-14
0=12x-12-14
0=12x-26
Flip the eqaution
12x-26=0
Move -26 across the equal sign
12x=0+26
12x=26
x=26/12
x=13/6
Hope this helps! A thanks/brainiest answer would be appreciated :)
Answer:
1 / ( 243s^40 )
Step-by-step explanation:
For this problem, we need to know that a negative exponent simply can be rewritten in the opposing part of the fraction, for this case, the denominator. So we can simplify as shown:
(3s^8)^-5
= 1 / (3s^8)^5
= 1 / 3^5 * s^8^5
= 1 / 243 * s^40
= 1 / ( 243s^40 )
Cheers.
70+75+80+90+100=415
415/5=83
<span>After the lowest grade is dropped, Janet's average would be an 83%</span>
120 ft... a flat vertical line is 180 degrees, and since this is a 30,60,90 triangle, your equation is... 180-60=distance John is to the base
Each person would get 1 and left overs r in the trash lel